Susceptibility of Bordetella species to growth inhibition and killing by chlorpromazine. - Hewlett, E L (1983)
Chlorpromazine, the prototype phenothiazine tranquilizer, inhibited the growth and killed organisms of the genus Bordetella. There were striking differences, however, among the three Bordetella species. Bordetella pertussis was most susceptible, with some inhibition of growth at greater than or equal to 4 micrograms/ml and killing at 16 micrograms of chlorpromazine per ml. Bordetella parapertussis and Bordetella bronchiseptica were less susceptible, with killing at 32 and 256 micrograms/ml, respectively. Although the phenothiazines were inhibitory for Bordetella extracytoplasmic adenylate cyclase, the lethal effect occurred at a lower concentration and did not appear to involve modification of the enzyme activity. Exposure of B. pertussis to combinations of chlorpromazine and erythromycin resulted in impaired growth at concentrations lower than that of either drug alone, but there was no evidence that the two drugs interacted either synergistically or antagonistically.